ON THE PATH TO THE EU: STRENGTHENING ECONOMIC RESILIENCE OF UKRAINE’S JUSTICE AREA - Tetiana Kolomoiets; Olena Agapova; Marcin Orzechowski (Baltic Journal of Economic Studies)
This study examines the process of integrating public administration entities within the Justice Area into the European Union's legal and administrative framework, with a particular focus on the economic dimensions of these transformations. It is widely acknowledged that the enhancement of administrative and legal regulation is of paramount importance for the attainment of EU membership, as it serves to promote both institutional efficiency and economic stability. The accelerated legislative adaptation amidst the ongoing war serves to illustrate Ukraine's resilience in aligning its governance structures with EU standards, with the objective of improving public administration efficiency, human rights protections and economic sustainability. The research identifies key reforms in the justice sector, including the digitalisation of legal aid, modernisation of the penitentiary system and streamlining of the notarial process. These reforms are not only advancements in the judicial system but also strategic steps to attract foreign investment by improving the rule of law and reducing corruption. The economic benefits of these reforms include increased investor confidence, more optimal resource allocation within the justice system, and cost reductions through digital transformations. The study's key findings highlight the role of public administration entities in fostering economic stability. For example, reforms in insolvency and restructuring, in accordance with EU Directive 2019/1023, serve to enhance the resilience and efficiency of the business climate. Furthermore, initiatives to modernise forensic services and digitise justice processes have the additional benefit of reducing systemic costs, thereby promoting transparency and economic competitiveness. The study reaches the conclusion that Ukraine's integration into the European Justice Area is as much an economic endeavour as it is a legal and administrative one. The reinforcement of public administration mechanisms in the justice sector serves to bolster macroeconomic stability, facilitate sustainable development and position Ukraine as a pivotal economic partner within the European legal and financial ecosystem. These endeavours illustrate a dedication to harmonising governance and economic frameworks with EU standards, thereby ensuring mutual benefits for both Ukraine and the EU.